APPLICATION OF FINANCING AGREEMENT ON SHARIA BANKING IN THE FORM OF NOTARY DEED - M Syukran Yamin Lubis (Proceeding International Seminar of Islamic Studies, 2021)
Financing based on sharia principles is the provision of money or claims equivalent to that based on an agreement or agreement between the Bank and another party and requires the financed party to return the money or claim after a certain period of time with compensation or profit sharing. Through normative juridical research methods, it can be concluded that In practice, financing schemes at Islamic banks are generally made in the form of notarial deeds. Making sharia financing agreements in the form of notarial deeds all this time still refers to the Law of Notary Position, not yet specifically stipulated sharia contract documents (contracts) in the form of notary deeds, Islamic financing in Indonesia still uses conventional guarantee institutions such as dependents and fiduciary rights not yet based on on sharia guarantees, although sharia bank products are based on Islamic law, for agreements/ agreements it can be made by a notary who is not a Muslim, specifically the relationship with witnesses in making a notary deed in positive law in Indonesia is different from Islamic law In positive law in Indonesia, the position of male and female witnesses is the same, whereas testimony in an agreement according to Islamic law must pay attention to the provisions in Al Qur'an, Surat Al Baqarah verse 282 which states that two male witnesses should be witnessed, if there are no witnesses two men, the witness can do it with a man and two women.Keywords: Sharia Financing Agreement, Sharia Banking, Notarial Deed